Work Compatibility of Excavator Komatsu PC400 with Hino 500 FM 320 TI Transport Equipment in Coal Mining Activities in North Pit Muara Tiga Besar 1 PT Bukit Asam, Tbk.Tanjung Enim, South Sumatra. - Muhammad Fajar Ramadhan (Journals Mining Engineering : Bina Tambang, 2024)
PT Bukit Asam (Persero) Tbk is a State-Owned Enterprise (SOE) established on March 2, 1981 located in Tanjung Enim, South Sumatra. The purpose of production activities is to produce minerals that have a price or selling value, in coal production activities there are two productions that can be done, namely coal production and overburden production. PT Bukit Asam Tbk. applies the open pit mining method. In coal getting activities, PT Bukit Asam Tbk. uses Komatsu PC400 excavating equipment and DT HINO 500 transportation equipment, while in overburden excavation activities PT Bukit Asam Tbk. uses Komatsu PC2000 excavating equipment and Komatsu HD785 transportation equipment. Apart from loading and hauling excavation equipment as the main mining equipment, there are also supporting equipment such as motor graders, bulldozers, water tanks and fuel tanks to get optimal and maximum results from production. In coal mining activities in the Muara Tiga Besar Mining area, PT Bukit Asam Tbk. company uses Komatsu PC 400 for coal getting and Komatsu PC2000 for overburden activities, while for transportation equipment in the form of Dump Trcuk HINO 500 FM 320 TI for coal getting and HD 785 for overburden activities. The results of observations in the field obtained the productivity value of the PC400 digging tool for coal getting is 257.73 tons / hour, while for DT HINO 500 FM 320 TI for coal getting is 72.46 tons / hour.